PEDOT dispersions with high power index N
By adjusting the power-law exponent of the polythiophene and polyanionic complex dispersions and through high-voltage homogenization, a low-ESR solid electrolyte layer was prepared, solving the problem of high ESR in existing electrolyte capacitors and improving the conductivity of the capacitor.
Patent Information
- Application Number
- CN202480030307.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-05-16
- Filing Date
- 2024-05-15
- Publication Date
- 2025-12-12
AI Technical Summary
In the prior art, electrolyte capacitors with solid electrolyte layers prepared based on PEDOT/PSS dispersions have high equivalent series resistance (ESR), which cannot meet the requirements of some applications.
A dispersion with low ESR was prepared by using a dispersion containing polythiophene and a polyanionic complex, adjusting the power law exponent n in the Ostwald de Waele relation to the range of 0.62 to 0.92, and homogenizing it under high pressure.
It significantly reduces the equivalent series resistance of the solid electrolyte layer, improves the conductivity of the capacitor, and meets the performance requirements of specific applications.
Smart Images

Figure CN121127936A_ABST
Abstract
Description
[0001] Description TECHNICAL FIELD
[0002] The present invention relates to a dispersion comprising a dispersant and at least one polythiophene dispersed in the dispersant, to a method for producing a dispersion, to a dispersion obtainable by the method, to a method for producing a layered body, to a layered body obtainable by the method, and to the use of the dispersion for forming a solid electrolyte layer in a capacitor. BACKGROUND
[0003] Standard electrolytic capacitors are usually composed of a porous metal electrode, an oxide layer arranged on the metal surface, an electrically conductive material (usually solid) introduced into the porous structure, an external electrode (contact) such as a silver layer and other electrical contacts and encapsulations. One frequently used electrolytic capacitor is a tantalum electrolytic capacitor whose anode electrode is made of the valve metal tantalum on which a uniform tantalum pentoxide dielectric layer has been produced by anodization, also called "forming". A liquid or solid electrolyte forms the cathode of the capacitor. Also frequently used are aluminum capacitors whose anode electrode is made of the valve metal aluminum on which a uniform electrically insulating aluminum oxide layer has been produced as a dielectric by means of anodization. Here, in addition, a liquid electrolyte or a solid electrolyte forms the cathode of the capacitor. Aluminum capacitors are usually embodied as wound capacitors or stacked capacitors.
[0004] In view of their high electrical conductivity, - conjugated polymers are particularly suitable as solid electrolytes in the above-mentioned capacitors. - Conjugated polymers are also known as conductive polymers or synthetic metals. They are gaining increasing commercial significance because, in comparison with metals, polymers have advantages in terms of processing, weight and selective adjustment of properties by chemical modification. Known Examples of conjugated polymers include polypyroles, polythiophenes, polyanilines, polyacetylenes, polyphenylenes and poly(p-phenylene-vinylene), wherein poly(3,4-ethylenedioxythiophene) (PEDOT) is a particularly important polythiophene used in technology because it has a very high electrical conductivity in its oxidized form.
[0005] Therefore, in the prior art, alternative methods have been developed for manufacturing solid electrolytes based on conductive polymers in electrolytic capacitors. For example, DE-A-10 2005 043 828 describes a method for manufacturing a solid electrolyte in a capacitor, in which a dispersion comprising a polythiophene (for example, a PEDOT / PSS dispersion known from the prior art) is applied to the oxide layer and the dispersion medium is then removed by evaporation.
[0006] However, it has been observed that the equivalent series resistance (ESR) of electrolytic capacitors having a solid electrolyte layer prepared using conventional PEDOT / PSS dispersions is often too high for certain applications.
[0007] The present application is based on the object of overcoming the disadvantages related to capacitors, preferably electrolytic capacitors, more preferably capacitors known from the prior art comprising a solid electrolyte layer based on - conjugated polymers such as PEDOT, even more preferably the disadvantages related to capacitors known from the prior art comprising a solid electrolyte layer based on PEDOT / PSS.
[0008] In particular, the present application is based on the object of providing dispersions comprising at least one polythiophene, preferably dispersions comprising a complex of a polythiophene and a polyanion, more preferably dispersions comprising a PEDOT / PSS complex, which are particularly useful for preparing a solid electrolyte layer in a capacitor featuring a low ESR.
[0009] It is a further object of the present application to provide a process by means of which such advantageous dispersions can be prepared. The process for preparing the advantageous dispersions should be characterized in that it allows for manufacturing these dispersions in the possibly simplest manner.
[0010] Furthermore, it is an object of the present application to provide a process for preparing a layered body, preferably for preparing an electrolytic capacitor, wherein the electrolytic capacitor features a reduced ESR compared to electrolytic capacitors known from the prior art. SUMMARY
[0011] The independent claims contribute at least in part to solving at least one of the above-mentioned objects, preferably more than one. The dependent claims provide preferred embodiments which contribute to solving at least one of the objects at least in part.
[0012] The first embodiment of the dispersion contributes to solving at least one of the objects according to the present application, which comprises:
[0013] i) a dispersant (also referred to as "dispersing agent");
[0014] ii) at least one polythiophene dispersed in the dispersant i);
[0015] wherein for the dispersion the power law index n in the Ostwald de Waele relationship
[0016]
[0017] The value is in the range of 0.62 to 0.92, preferably in the range of 0.66 to 0.88, more preferably in the range of 0.70 to 0.84, and even more preferably in the range of 0.72 to 0.82, wherein It is shear stress, K is the flow consistency index, and It is the shear rate dγ / dt; and
[0018] The dispersion has a solids content of at least 1.5% by weight, preferably at least 1.6% by weight, more preferably at least 1.7% by weight, and even more preferably at least 1.8% by weight, based on the total weight of the dispersion in each case.
[0019] In the context of this invention, the term "dispersion" generally refers to any liquid composition (dispersant i) in which polythiophene (e.g., polythiophene as part of a complex comprising polythiophene and a polyanion) is distributed in a certain way in a homogeneous phase formed by a liquid dispersant i, thus forming a dispersion (the liquid phase). It should be noted that the transition between "dispersion" and "solution" can be fluid. For this reason, no distinction is made below between the terms "dispersed" and "dissolved." Similarly, no distinction is made between "dispersion" and "solution" or between "dispersant" and "solvent." Rather, these terms are used synonymously below.
[0020] According to a preferred embodiment of the dispersion according to the invention, the dispersant i) comprises water. Preferably, the dispersant i) comprises at least 50% by weight, more preferably at least 65% by weight, even more preferably at least 70% by weight, and most preferably at least 80% by weight of water based on the total weight of the dispersion in each case. This preferred embodiment is a second embodiment of the dispersion according to the invention, which preferably depends on the first embodiment.
[0021] According to another preferred embodiment of the dispersion according to the invention, the at least one polythiophene (ii) is an externally doped polythiophene such as cationic polythiophene existing in the form of a polythiophene / polyanionic complex, more preferably in the form of a PEDOT / PSS complex, a self-doped polythiophene such as poly(4-[(2,3-dihydrothieno[3,4-b][1,4]dioxane-2-yl)methoxy]propane-1-sulfonic acid), poly(4-[(2,3-dihydrothieno[3,4-b][1,4]dioxane-2-yl)methoxy]butane-1-sulfonic acid) (PEDOT-S) or poly(4-[(2,3-dihydrothieno[3,4-b][1,4]dioxane-2-yl)methoxy]butane-2-sulfonic acid), or a mixture thereof. This preferred embodiment is a third embodiment of the dispersion according to the invention, which preferably depends on the first or second embodiment.
[0022] According to another preferred embodiment of the dispersion according to the invention, the at least one polythiophene (ii) exists in the form of particles comprising a complex of the at least one polythiophene (ii) and a polyanion. This preferred embodiment is a fourth embodiment of the dispersion according to the invention, which preferably depends on any one of the first to third embodiments.
[0023] According to another preferred embodiment of the dispersion according to the invention, the at least one polythiophene (ii) exists in the form of particles comprising a complex of the at least one polythiophene (ii) and a polyanion, wherein the polythiophene is poly(3,4-ethylenedioxythiophene) and the polyanion is an anion of polystyrene sulfonate. Therefore, the polythiophene-polyanion complex is preferably a PEDOT / PSS complex. This preferred embodiment is a fifth embodiment of the dispersion according to the invention, which preferably depends on any one of the first to fourth embodiments.
[0024] According to another preferred embodiment of the dispersion according to the invention, the at least one polythiophene (ii) is present in the form of particles comprising a complex of the at least one polythiophene (ii) and a polyanion, preferably in the form of particles comprising PEDOT / PSS, wherein the weight ratio of the polyanion to the polythiophene in the dispersion is in the range of 0.5:1 to 30:1, preferably in the range of 0.8:1 to 15:1, more preferably in the range of 1:1 to 10:1, even more preferably in the range of 1.2:1 to 8:1, and most preferably in the range of 1.4:1 to 4:1. In this context, assuming complete conversion occurs during polymerization, the weight of the polythiophene corresponds to the weighing of the thiophene monomer used to prepare the polythiophene. This preferred embodiment is a sixth embodiment of the dispersion according to the invention, which preferably depends on any one of the first to fifth embodiments.
[0025] According to another preferred embodiment of the dispersion according to the invention, the at least one polythiophene (ii) exists in the form of particles comprising a complex of the at least one polythiophene (ii) and a polyanion, preferably in the form of particles comprising PEDOT / PSS, wherein the weight-average diameter (d) of these particles is determined by ultracentrifugation measurements. 50 The dispersion is in the range of 1 nm to 100 nm, more preferably in the range of 2 nm to 50 nm, even more preferably in the range of 3 nm to 40 nm, and most preferably in the range of 4 nm to 30 nm. This preferred embodiment is a seventh embodiment of the dispersion according to the invention, which preferably depends on any one of the first to sixth embodiments.
[0026] According to another preferred embodiment of the dispersion according to the invention, the at least one polythiophene (ii) exists in the form of particles comprising a complex of the at least one polythiophene (ii) and a polyanion, preferably in the form of particles comprising PEDOT / PSS, wherein the diameter distribution of these particles in the dispersion, as determined by ultracentrifugation, is d 90 The value is less than 100 nm, preferably less than 80 nm, more preferably less than 60 nm, and most preferably less than 50 nm. This preferred embodiment is an eighth embodiment of the dispersion according to the invention, which preferably depends on any one of the first to seventh embodiments.
[0027] According to another preferred embodiment of the dispersion according to the invention, the at least one polythiophene (ii) exists in the form of particles comprising a complex of the at least one polythiophene (ii) and a polyanion, preferably in the form of particles comprising PEDOT / PSS, wherein the dispersion is such that the diameter distribution of these particles is determined by ultracentrifugation measurement. 10 The value is greater than 1 nm, preferably greater than 2 nm, more preferably greater than 3 nm, and most preferably greater than 4 nm. This preferred embodiment is a ninth embodiment of the dispersion according to the invention, which preferably depends on any one of the first to eighth embodiments.
[0028] According to another preferred embodiment of the dispersion according to the invention, the pH value of the dispersion (determined at 25°C) is in the range of 2.5 to 8.0, preferably in the range of 2.5 to 7, and more preferably in the range of 3 to 6. This preferred embodiment is a tenth embodiment of the dispersion according to the invention, which preferably depends on any one of the first to ninth embodiments.
[0029] According to another preferred embodiment of the dispersion according to the invention, the at least one polythiophene (ii) is present in the form of particles comprising a complex of the at least one polythiophene (ii) and a polyanion, preferably in the form of particles comprising PEDOT / PSS, wherein the total amount of the polythiophene and the polyanion contained in the dispersion (i.e., the amount of polythiophene plus the amount of polyanion) is at least 1.5% by weight, preferably at least 1.6% by weight, more preferably at least 1.7% by weight, and most preferably at least 1.8% by weight, based on the total weight of the dispersion in each case. This preferred embodiment is an eleventh embodiment of the dispersion according to the invention, which preferably depends on any one of the first to tenth embodiments.
[0030] According to another preferred embodiment of the dispersion according to the invention, the dispersion further comprises:
[0031] iii) at least one additive, wherein the at least one additive is an additive selected from the group consisting of: binders, pH adjusters, crosslinking agents, adhesion promoters, conductivity improvers, surfactants, stabilizers, and combinations of at least two of these additives.
[0032] This preferred embodiment is the twelfth embodiment of the dispersion according to the invention, which preferably depends on any one of the first to eleventh embodiments.
[0033] According to another preferred embodiment of the dispersion according to the invention, the viscosity of the dispersion (at 20°C and in 100s) is... -1 The shear rate (measured by a rheometer) is in the range of 0.1 mPa×s to 200 mPa×s, preferably in the range of 1 mPa×s to 100 mPa×s, more preferably in the range of 5 mPa×s to 70 mPa×s, and most preferably in the range of 10 mPa×s to 50 mPa×s. This preferred embodiment is a thirteenth embodiment of the dispersion according to the invention, which preferably depends on any one of the first to twelfth embodiments.
[0034] According to another preferred embodiment of the dispersion according to the invention, the conductive layer prepared from the dispersion has a conductivity greater than 10 S / cm, preferably greater than 50 S / cm, more preferably greater than 100 S / cm, even more preferably greater than 200 S / cm, and most preferably greater than 300 S / cm, determined in each case by the test method disclosed herein (i.e., by a test method wherein the conductivity of the conductive layer is determined for a dispersion obtained after 19 g of the dispersion according to the invention has been supplemented with 1 g of DMSO). This preferred embodiment is a fourteenth embodiment of the dispersion according to the invention, which preferably depends on any one of the first to thirteenth embodiments.
[0035] A first embodiment of method 1 for preparing a dispersion also contributes to solving at least one of the objectives according to the invention, the method comprising the following steps:
[0036] I) Provides a dispersion comprising:
[0037] i) Dispersant;
[0038] ii) At least one polythiophene dispersed in the dispersant i);
[0039] Thiophene monomers are polymerized in the presence of dispersant i) and oxidant, wherein the molar ratio of oxidant to thiophene monomer is 1:1 to 1.3:1 before polymerization;
[0040] The dispersion has a solid content of at least 1.5% by weight, preferably at least 1.6% by weight, more preferably at least 1.7% by weight, and even more preferably at least 1.8% by weight, based on the total weight of the dispersion in each case;
[0041] Furthermore, the dispersion has a conductivity greater than 10 S / cm, preferably greater than 50 S / cm, more preferably greater than 100 S / cm, even more preferably greater than 200 S / cm, and most preferably greater than 300 S / cm, which is determined in each case by the test methods disclosed herein;
[0042] II) Adjust the power law exponent n in the dispersion provided in step I) to be in the range of 0.62 to 0.92, preferably in the range of 0.66 to 0.88, more preferably in the range of 0.70 to 0.84, and even more preferably in the range of 0.72 to 0.82.
[0043] According to a preferred embodiment of method 1 according to the invention, the dispersant i) comprises water. Preferably, the dispersant i) comprises at least 50% by weight, more preferably at least 65% by weight, even more preferably at least 70% by weight, and most preferably at least 80% by weight of water based on the total weight of the dispersion in each case. This preferred embodiment is a second embodiment of method 1 according to the invention, which preferably depends on the first embodiment.
[0044] According to another preferred embodiment of method 1 of the present invention, the thiophene monomer is polymerized in the presence of the dispersant i) and the polyanion to obtain a dispersion comprising a complex of polythiophene and the polyanion. This preferred embodiment is a third embodiment of method 1 of the present invention, which preferably depends on the first embodiment or the second embodiment.
[0045] According to another preferred embodiment of method 1 of the present invention, the thiophene monomer is polymerized in the presence of the dispersant i) and the polyanion to obtain a dispersion comprising a complex of polythiophene and a polyanion, wherein the thiophene monomer is 3,4-ethylenedioxythiophene and the polyanion is an anion of polystyrene sulfonate. Therefore, the polythiophene-polyanion complex is preferably a PEDOT / PSS complex. This preferred embodiment is a fourth embodiment of method 1 of the present invention, which preferably depends on any one of the first to third embodiments.
[0046] According to another preferred embodiment of method 1 of the present invention, polythiophene is included in the dispersion obtained in step I) of method in an amount ranging from 12% to 40% by weight based on the total weight of polythiophene and polyanion in the dispersion. This preferred embodiment is a fifth embodiment of method 1 of the present invention, which preferably depends on the fourth embodiment.
[0047] According to another preferred embodiment of method 1 of the present invention, the adjustment of the power law exponent n in the dispersion provided in step I) is achieved by subjecting the dispersion provided in step I) to homogenization, preferably high-pressure homogenization, even more preferably at a pressure of at least 1,000 bar, preferably at a pressure of at least 1,200 bar, more preferably at a pressure of at least 1,400 bar, even more preferably at a pressure of at least 1,600 bar, and most preferably at a pressure of at least 1,800 bar, in a series of at least 25, preferably at least 35, more preferably at least 45, even more preferably at least 55, and most preferably at least 65 high-pressure homogenization steps. This preferred embodiment is a sixth embodiment of method 1 according to the present invention, which preferably depends on any one of the first to fifth embodiments.
[0048] According to another preferred embodiment of method 1 of the present invention, the thiophene monomer is polymerized in the presence of the dispersant i) and the polyanion to obtain a dispersion comprising a complex of polythiophene and a polyanion, wherein the thiophene monomer is 3,4-ethylenedioxythiophene and the polyanion is the anion of polystyrene sulfonic acid.
[0049] - The molar ratio of oxidant to thiophene monomer before polymerization is in the range of 1.09:1 to 1.13:1;
[0050] - Polythiophene is included in the dispersion obtained in step I of method in an amount ranging from 27% to 30% by weight, based on the total weight of polythiophene and polyanion in the dispersion;
[0051] - The adjustment of the power law exponent n in the dispersion provided in method step I) is achieved by subjecting the dispersion provided in method step I) to a series of at least 55 high-pressure homogenization steps performed at a pressure of at least 1,400 bar.
[0052] This preferred embodiment is a seventh embodiment of method 1 according to the present invention, which preferably depends on any one of the first to sixth embodiments.
[0053] According to another preferred embodiment of method 1 of the present invention, the thiophene monomer is polymerized in the presence of the dispersant i) and the polyanion to obtain a dispersion comprising a complex of polythiophene and a polyanion, wherein the thiophene monomer is 3,4-ethylenedioxythiophene and the polyanion is the anion of polystyrene sulfonic acid.
[0054] - The molar ratio of oxidant to thiophene monomer before polymerization is in the range of 1.09:1 to 1.13:1;
[0055] - Polythiophene is included in the dispersion obtained in step I of method in an amount ranging from 13% to 15% by weight, based on the total weight of polythiophene and polyanion in the dispersion;
[0056] - The adjustment of the power law exponent n in the dispersion provided in method step I) is achieved by subjecting the dispersion provided in method step I) to a series of at least 55 high-pressure homogenization steps performed at a pressure of at least 1,400 bar.
[0057] This preferred embodiment is the eighth embodiment of method 1 according to the present invention, which preferably depends on any one of the first to sixth embodiments.
[0058] According to another preferred embodiment of method 1 of the present invention, the thiophene monomer is polymerized in the presence of the dispersant i) and the polyanion to obtain a dispersion comprising a complex of polythiophene and a polyanion, wherein the thiophene monomer is 3,4-ethylenedioxythiophene and the polyanion is the anion of polystyrene sulfonic acid.
[0059] - The molar ratio of oxidant to thiophene monomer before polymerization is in the range of 1.20:1 to 1.24:1;
[0060] - Polythiophene is included in the dispersion obtained in step I of method in an amount ranging from 27% to 30% by weight, based on the total weight of polythiophene and polyanion in the dispersion;
[0061] - The adjustment of the power law exponent n in the dispersion provided in method step I) is achieved by subjecting the dispersion provided in method step I) to a series of at least 55 high-pressure homogenization steps performed at a pressure of at least 1,400 bar.
[0062] This preferred embodiment is the ninth embodiment of method 1 according to the present invention, which preferably depends on any one of the first to eighth embodiments.
[0063] The dispersion also contributes to achieving at least one of the objectives according to the invention, and the dispersion can be obtained by method 1 according to the invention, preferably by method 1 according to any one of the first to ninth embodiments. Preferably, the dispersion has the same properties as the dispersion according to the invention, and preferably the same properties as the dispersion according to the invention as defined in any one of the first to fourteenth embodiments.
[0064] A first embodiment of method 2 for preparing a lamellar body also contributes to solving at least one of the objectives according to the invention, the method comprising the following steps:
[0065] A) Provide the substrate;
[0066] B) Apply the dispersion according to the invention, preferably the dispersion according to the invention as defined in any one of the first to fourteenth embodiments, or the dispersion that can be obtained by method 1 according to the invention, preferably by method 1 as defined in any one of the first to ninth embodiments, to at least a portion of the surface of the substrate;
[0067] C) At least partially remove the dispersant i) to obtain a layer comprising a conductive layer coated on at least a portion of the surface of the substrate.
[0068] According to a preferred embodiment of method 2 of the present invention, the layered body is part of a solid electrolyte capacitor, wherein the substrate is a porous electrode body made of an electrode material, wherein the dielectric layer at least partially covers the surface of the electrode material, and wherein the conductive layer is a solid electrolyte layer at least partially covering the surface of the dielectric layer. This preferred embodiment is a second embodiment of method 2 of the present invention, which preferably depends on the first embodiment.
[0069] According to a preferred embodiment of method 2 of the present invention, the method includes the following steps:
[0070] A) Provides a porous electrode body made of an electrode material, wherein a dielectric layer at least partially covers the surface of the electrode material;
[0071] B) Introduce the dispersion according to the invention, preferably the dispersion according to the invention as defined in any one of the first to fourteenth embodiments, or the dispersion that can be obtained by method 1 according to the invention, preferably by method 1 as defined in any one of the first to ninth embodiments, into at least a portion of the porous electrode body provided in step A) of the method, so as to apply the dispersion to at least a portion of the surface of the dielectric layer.
[0072] C) At least partially remove the dispersant i) to form a solid electrolyte that at least partially covers the surface of the dielectric layer;
[0073] D) Optionally, a dispersion containing a conductive polymer, preferably a dispersion containing polythiophene and a dispersant, more preferably a dispersion containing a dispersant and particles of a complex of polythiophene and a polymer anion, or even more preferably a PEDOT / PSS dispersion, is applied to at least a portion of the surface of the solid electrolyte layer, and the dispersant is at least partially removed to form a polymer outer layer that at least partially covers the surface of the solid electrolyte layer.
[0074] This preferred embodiment is a third embodiment of method 2 according to the present invention, which preferably depends on the first embodiment or the second embodiment.
[0075] According to another preferred embodiment of method 2 of the present invention, the layered body is an aluminum capacitor or a tantalum capacitor. This preferred embodiment is a fourth embodiment of method 2 of the present invention, which preferably depends on any one of the first to third embodiments.
[0076] The layered structure also contributes to achieving at least one of the objectives according to the invention, which can be obtained by method 2 according to the invention, preferably by method 2 according to any one of its first to fourth embodiments.
[0077] The use of the dispersion according to the invention, preferably the dispersion according to the invention as defined in any one of the first to fourteenth embodiments, or the dispersion that can be obtained by method 1 according to the invention, preferably by method 1 as defined in any one of the first to ninth embodiments, for forming a solid electrolyte layer in a capacitor also contributes to solving at least one of the objectives according to the invention.
[0078] According to a preferred embodiment of the application of the invention, the capacitor is an aluminum capacitor or a tantalum capacitor. This preferred embodiment is a second embodiment of the application of the invention, which preferably depends on the first embodiment. Detailed Implementation
[0079] Polythiophene
[0080] The dispersion according to the invention comprises a dispersant and at least one polythiophene dispersed in the dispersant.
[0081] Preferred polythiophenes are those having repeating units of general formula (I), general formula (II), or general formula (III), or combinations thereof:
[0082]
[0083] in
[0084] A is an optionally substituted C1-C5-alkylene group.
[0085] R is independently H, a linear or branched, optionally substituted C1-C 18 -alkyl group, optionally substituted C5-C 12 - Cycloalkyl group, optionally substituted C6-C 14 -Aryl group, optionally substituted C7-C 18 -Aryl group, optionally substituted C1-C4-hydroxyalkyl group or hydroxy group,
[0086] x is an integer from 0 to 8, and
[0087] When multiple R groups are bonded to A, they can be the same or different.
[0088] General formulas (I) and (II) should be understood as allowing the x-substituent R to bond with the alkylene group A.
[0089] Particularly preferred polythiophenes have repeating units of general formula (I) or (II), or repeating units of general formulas (I) and (II), wherein A is an optionally substituted C2-C3-alkylene group and x is 0 or 1. Very particularly preferred polythiophenes are poly(3,4-ethylenedioxythiophene) (PEDOT), which is optionally substituted with poly(4-[(2,3-dihydrothieno[3,4-b][1,4]dioxane-2-yl)methoxy]propane-1-sulfonic acid), poly(4-[(2,3-dihydrothieno[3,4-b][1,4]dioxane-2-yl)methoxy]butane-1-sulfonic acid) (PEDOT-S) or poly(4-[(2,3-dihydrothieno[3,4-b][1,4]dioxane-2-yl)methoxy]butane-2-sulfonic acid).
[0090] In the context of this invention, the prefix "poly" should be understood to refer to the presence of more than one identical or different repeating unit in the polymer or polythiophene. The polythiophene comprises a total of n repeating units of general formula (I), or general formula (II), or general formula (III), or general formulas (I) and (II), or general formulas (I) and (III), or general formulas (II) and (III), or general formulas (I), (II), and (III), where n is an integer from 2 to 2000, preferably from 2 to 100. The repeating units of general formula (I), or general formula (II), or general formula (III), or repeating units of general formulas (I) and (II), or repeating units of general formulas (I) and (III), or repeating units of general formulas (II) and (III), or repeating units of general formulas (I), (II), and (III) may each be identical or different in the polythiophene. Preferred polythiophenes have the same repeating unit of general formula (I), general formula (II), or general formula (III) in each case, or the same repeating unit of general formula (I) and (II), or general formula (I) and (III), or general formula (II) and (III) in each case, or the same repeating unit of general formula (I), (II), and (III) in each case. Particularly preferred polythiophenes have the same repeating unit of general formula (I) or general formula (II) in each case, or the same repeating unit of general formula (I) and (II) in each case. At the end groups, the polythiophenes preferably each carry H.
[0091] In the context of this invention, the C1-C5-alkylene group A is preferably methylene, ethylene, n-propylene, n-butylene, or n-pentylene. 18 -alkyl group R is preferably a straight-chain or branched C1-C group. 18 -alkyl groups, such as methyl, ethyl, n-propyl or isopropyl, n-butyl, isobutyl, sec-butyl or tert-butyl, n-pentyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 1-ethylpropyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 2,2-dimethylpropyl, n-hexyl, n-heptyl, n-octyl, 2-ethylhexyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-hexadecyl or n-octadecyl, C5-C 12 -The cycloalkyl group R is, for example, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, or cyclodecyl, C6-C 14 -The aryl group R is, for example, phenyl or naphthyl, and C7-C 18The aryl group R is, for example, benzyl, o-tolyl, m-tolyl, p-tolyl, 2,3-xylyl, 2,4-xylyl, 2,5-xylyl, 2,6-xylyl, 3,4-xylyl, 3,5-xylyl, or mesitylene. The foregoing examples are for illustrative purposes only and should not be considered exclusive.
[0092] In the context of this invention, any additional substituents of the A group and / or R group include a number of organic groups, such as alkyl, cycloalkyl, aryl, aralkyl, alkoxy, halogen, ether, thioether, disulfide, sulfoxide, sulfone, sulfonate, amino, aldehyde, ketone, carboxylic acid ester, carboxylic acid, carbonate, carboxylic acid ester, cyano, alkylsilane and alkoxysilyl groups, as well as formamide groups.
[0093] Polythiophenes can be uncharged or cationic. In preferred embodiments, they are cationic, and "cationic" refers only to the charge remaining on the main polythiophene chain. Depending on the substituents on the R groups, polythiophenes can carry both positive and negative charges within the structural units, in which case the positive charge is on the polythiophene backbone and the negative charge (if present) is on the R groups substituted with sulfonate or carboxylate groups. The positive charge on the polythiophene backbone can be partially or completely saturated by anionic groups that may be present on the R groups. In general, polythiophenes in these cases can be cationic, uncharged, or even anionic. However, in the context of this invention, all are considered cationic polythiophenes because the positive charge on the polythiophene backbone is crucial. The positive charge is not shown in the formula because its precise quantity and location cannot be explicitly represented. However, the number of positive charges is at least 1 and at most n, where n is the total number of all repeating units (identical or different) within the polythiophene.
[0094] The positive charge of polythiophene can be balanced by R groups that are substituted with sulfonates or carboxylates and are therefore negatively charged (so-called "self-doped polythiophene") or by counterions (so-called "externally doped polythiophene").
[0095] According to a first preferred embodiment of the polythiophene in the dispersion according to the invention, the polythiophene is a self-doped polythiophene, which preferably comprises at least 50%, more preferably at least 75%, more preferably at least 95%, and most preferably 100% of repeating units of formula (IV).
[0096]
[0097] in
[0098] X and Y are the same or different, and represent O, S, NR. 1 ,
[0099] Where R 1 Indicates aryl, C1-C 18 -alkyl or hydrogen;
[0100] Z is an organic group carrying an anionic functional group, preferably SO3. - The group, particularly preferred being Z representing -(CH2). m -CR 2 R 3 -(CH2) n -,
[0101] R 2 It represents hydrogen, -(CH2). s -O-(CR 4 2) p -SO3 - M + Or -(CH2) p -SO3 - M + ,
[0102] R 3 It represents -(CH2) s -O-(CR 4 2) p -SO3 - M + Or -(CH2) p -SO3 - M + ,
[0103] M + Indicates a cation.
[0104] m and n can be the same or different, and represent integers from 0 to 3.
[0105] R 4 Indicates hydrogen or C1-C 10 Alkyl groups, preferably methyl groups,
[0106] s represents an integer from 0 to 10, and
[0107] p represents an integer from 1 to 18.
[0108] In this context, the percentage figures above are intended to represent the numerical content of units of structural formula (IV) out of the total number of monomer units in a self-doped conductive polymer.
[0109] Suitable cation M + For example, H + Li + Na + K + 、Rb+ Cs + and NH4 + A particularly suitable cation is Na. + and K + .
[0110] A particularly preferred monomer of structural formula (IV) is a monomer in which...
[0111] X and Y represent O,
[0112] Z represents ,
[0113] R 2 Indicates hydrogen or , or ,
[0114] R 3 express , or ,
[0115] M + Indicates a cation.
[0116] m and n can be the same or different, and represent integers from 0 to 3.
[0117] R 4 Indicates hydrogen, methyl group, or ethyl group;
[0118] s represents an integer from 0 to 10, and
[0119] p represents an integer from 1 to 18.
[0120] A particularly preferred monomer of structural formula (IV) is a monomer in which...
[0121] X and Y represent O,
[0122] Z represents ,
[0123] R 2 It represents hydrogen.
[0124] R 3 express , or or ,
[0125] M + Na represents + or K + ,
[0126] n represents 0 or 1,
[0127] s represents 0 or 1, and
[0128] p represents 2, 3, 4 or 5.
[0129] Suitable embodiments of self-doped polymers are disclosed in WO-A-2014 / 048562 and US-A-2015 / 0337061. Specific examples of very particularly preferred self-doped conductive polymers include poly(4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxane-2-yl)methoxy]propane-1-sulfonic acid), poly(4-[(2,3-dihydrothieno[3,4-b][1,4]dioxane-2-yl)methoxy]butane-1-sulfonic acid) (PEDOT-S), poly(4-[(2,3-dihydrothieno[3,4-b][1,4]dioxane-2-yl)methoxy]butane-2-sulfonic acid), or mixtures thereof.
[0130] According to a second preferred embodiment of the polythiophene in the dispersion according to the invention, the polythiophene is an externally doped polythiophene, which preferably contains a polymer counterion to balance the positive charge; the polymer counterion is also referred to hereinafter as a "polyanion". Therefore, according to a preferred embodiment of the dispersion according to the invention, the polythiophene is a cationic polythiophene containing a polyanion that acts as a counterion to the polythiophene.
[0131] Polyanions are preferred over monomeric anions because they facilitate film formation and, due to their size, result in more thermally stable conductive films. The polyanions herein can be, for example, anions of polymeric carboxylic acids (such as polyacrylic acid, polymethacrylic acid, or polymaleic acid) or polymeric sulfonic acids (such as polystyrene sulfonic acid and polyethylene sulfonic acid). These polycarboxylic acids and sulfonic acids can also be copolymers of ethylene carboxylic acid and ethylene sulfonic acid with other polymerizable monomers (such as acrylates and styrene).
[0132] Preferred polyanions are anions of polymeric carboxylic acids or sulfonic acids. Particularly preferred polyanions are anions of polystyrene sulfonic acid (PSS) or its derivatives.
[0133] The molecular weight of the polyanionic polyacid is preferably from 1,000 to 2,000,000, more preferably from 2,000 to 500,000. The polyacid or its alkali metal salt is commercially available, for example, polystyrene sulfonic acid and polyacrylic acid, or can be prepared by known processes (see, for example, Houben Weyl, Methods of Organischen Chemie, Vol. E 20, Makromolekulare Stoffe, Part 2, (1987), p. 1141 and subsequent pages).
[0134] A particularly preferred example of an externally doped polythiophene is a complex of poly(3,4-ethylenedioxythiophene) and polystyrene sulfonate anion (PEDOT / PSS).
[0135] Further additives
[0136] According to a preferred embodiment of the dispersion according to the invention, the dispersion further comprises at least one additive, wherein the at least one additive is an additive selected from the group consisting of: binders, pH adjusters, crosslinking agents, adhesion promoters, conductivity improvers, surfactants, stabilizers, and combinations of at least two of these additives.
[0137] Suitable binders include organic binders that are particularly soluble in organic solvents, such as polyolefins, polyvinyl acetate, polycarbonate, polyvinyl butyral, polyacrylate, polyacrylamide, polymethacrylate, polymethacrylamide, polystyrene, polyacrylonitrile, polyvinyl chloride, polyvinylpyrrolidone, polybutadiene, polyisoprene, polyether, polyester, polyurethane, polyamide, polyimide, polysulfone, polysiloxane, epoxy resin, styrene-acrylate, vinyl acetate / acrylate and ethylene / vinyl acetate copolymers, polyvinyl alcohol, or cellulose derivatives may also be added to the composition. Copolymers of the above polymers are also suitable as binders.
[0138] Suitable pH adjusters include, for example, the bases or acids described on page 4, lines 13-32 of WO 2010 / 003874 A2. Preferred additives are those that do not impair film formation of the dispersion and do not volatilize at relatively high temperatures (e.g., at welding temperatures), but remain within the solid electrolyte under these conditions. Particularly suitable are compounds such as the bases 2-dimethylaminoethanol, 2,2'-iminodiethanol, or 2,2',2'-nitrotriethanol and the acid polystyrene sulfonic acid.
[0139] Suitable crosslinking agents include melamine compounds, capped isocyanates, functional silanes (e.g., tetraethoxysilanes), alkoxysilane hydrolysis products (e.g., tetraethoxysilane-based hydrolysis products), or epoxysilanes (such as 3-glycidoxypropyltrialkoxysilane).
[0140] Suitable adhesion promoters include organofunctional silanes or their hydrolysis products, such as 3-glycidoxypropyltrialkoxysilane, 3-aminopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, vinyltrimethoxysilane, or octyltriethoxysilane.
[0141] Suitable conductivity improvers include compounds such as tetrahydrofuran, compounds containing lactone groups such as butyrolactone and valproic acid, compounds containing amide or lactam groups such as caprolactam, N-methylcaprolactam, N,N-dimethylacetamide, N-methylacetamide, N,N-dimethylformamide (DMF), N-methylformamide, N-methylformanilide, N-methylpyrrolidone (NMP), N-octylpyrrolidone, pyrrolidone, sulfones and sulfoxides such as sulfolane (tetramethylene sulfone) and dimethyl sulfoxide (DMSO), sugars or sugar derivatives such as sucrose, glucose, fructose, and lactose, sugar-based surfactants such as Tween or Span 60, sugar alcohols such as sorbitol and mannitol, furan derivatives such as 2-furancarboxylic acid and 3-furancarboxylic acid, and / or diols or polyols such as ethylene glycol, glycerol, diethylene glycol, triethylene glycol, or polyglycerol. Ethylene glycol, diethylene glycol, triethylene glycol, polyglycerol, dimethyl sulfoxide, or sorbitol are particularly preferred as conductivity-improving additives.
[0142] Suitable surfactants include: anionic surfactants, such as alkylbenzene sulfonic acids and salts, paraffin sulfonates, alcohol sulfonates, ether sulfonates, sulfosuccinates, phosphate esters, alkyl ether carboxylic acids, or carboxylates; cationic surfactants, such as quaternary alkylammonium salts; and nonionic surfactants, particularly nonionic amphiphilic surfactants, such as linear or branched alcohol ethoxylates, carbonyl synthetic alcohol ethoxylates, alkylphenol ethoxylates, or alkyl polyglucosides. Representative examples of suitable surfactants include fluorinated surfactants, such as ZONYL. ® Surfactants, including ZONYL ® FSN, ZONYL ® FSO, ZONYL ® FSA, ZONYL ® FSH (DuPont Chemicals, Wilmington, Del.) and NOVEC ® (3M, St. Paul, Minn.) Other exemplary surfactants include nonionic surfactants based on alkylphenol ethoxylates. Preferred surfactants include, for example, octylphenol ethoxylates such as TRITON. ® and secondary alcohol ethoxylates such as TERGITOL ® 15-S series (Dow Chemical Company, Midland Mich.). Other exemplary nonionic surfactants include acetylene-based surfactants, n-dodecyl β-D-maltodextrin, and alcohol ethoxylates, such as TERGITOL. ® TMN.
[0143] Suitable stabilizers are those compounds mentioned in WO 2012 / 041507 A1, with aromatic compounds containing at least two OH groups and an additional functional group having a heteroatom other than carbon being particularly preferred. Examples of suitable stabilizers are 3,4,5-trihydroxybenzoic acid and its derivatives, such as 3,4,5-trihydroxybenzoic acid esters (gallic acid esters), and will also be mentioned in particular alkyl esters, alkenyl esters, cycloalkyl esters, cycloalkenyl esters, and aryl esters, which in each case preferably have 1 to 15 carbon atoms in the aryl or alkyl group of the ester. Gallic acid and glycoesterified gallic acid are particularly preferred, which are commonly referred to as tannins or gallotannins (see Römpp Chemie, 10th edition (1999), p. 4391). Also suitable as stabilizers are “hydroxy-group-containing aromatic compounds” mentioned in paragraph
[0049] of EP 1 798 259 A1, “antioxidants” mentioned in paragraph
[0025] of EP 1 043 720 A1, and “aromatic compounds exclusive of sulfo groups and containing at least two hydroxy groups” mentioned on pages 10 and 11 of WO 2008 / 055834 A1.
[0144] Process for producing a capacitor
[0145] According to a preferred embodiment of the method for preparing a layered structure according to the present invention, the layered structure is part of an electrolyte capacitor. In this case, the method includes the following steps:
[0146] A) Provides a porous electrode body made of an electrode material, wherein a dielectric layer at least partially covers the surface of the electrode material;
[0147] B) Introduce the dispersion according to the invention, preferably the dispersion according to the invention as defined in any one of the first to fourteenth embodiments, or the dispersion that can be obtained by method 1 according to the invention, preferably by method 1 as defined in any one of the first to ninth embodiments, into at least a portion of the porous electrode body provided in step A) of the method, so as to apply the dispersion to at least a portion of the surface of the dielectric layer.
[0148] C) At least partially remove the dispersant i) to form a solid electrolyte layer that at least partially covers the surface of the dielectric layer;
[0149] D) Optionally, a dispersion containing a conductive polymer, preferably a dispersion containing polythiophene and a dispersant, more preferably a dispersion containing a dispersant and particles of a complex of polythiophene and a polymer anion, or even more preferably a PEDOT / PSS dispersion, is applied to at least a portion of the surface of the solid electrolyte layer, and the dispersant is at least partially removed to form a polymer outer layer that at least partially covers the surface of the solid electrolyte layer.
[0150] E) Optionally fill at least a portion of the pores of the porous electrode body (i.e., the porous electrode body in which the dielectric layer is at least partially covered by the solid electrolyte layer) obtained in step C) or step D) with an impregnation solution containing at least one impregnation solvent.
[0151] Method step A) :
[0152] In method step A), a porous electrode body made of an electrode material is provided, wherein a dielectric layer at least partially covers the surface of the electrode material.
[0153] In principle, the porous electrode body can be manufactured by pressing and sintering valve metal powder with a high surface area to form the porous electrode body. In this context, electrical contact wires, preferably made of valve metal (such as tantalum), are conventionally pressed into the porous electrode body. The porous electrode body is then coated, for example, by electrochemical oxidation with a dielectric, i.e., an oxide layer. Alternatively, a metal film can be etched and coated with an electrochemical oxidation dielectric to obtain an anode film with porous regions. In the case of a wound capacitor, the anode film with porous regions (which forms the electrode body) and the cathode film are separated by a separator and wound.
[0154] Within the scope of this invention, metals whose oxide coatings prevent the uniform flow of current in both directions are considered valve metals. When a voltage is applied to the anode, the oxide layer of a valve metal impedes current flow, while when a voltage is applied to the cathode, a considerable current can occur, which can destroy the oxide layer. Valve metals include Be, Mg, Al, Ge, Si, Sn, Sb, Bi, Ti, Zr, Hf, V, Nb, Ta, and W, as well as alloys or compounds of at least one of these metals with other elements. The most well-known representatives of valve metals are Al, Ta, and Nb. Combinations of electrical properties equivalent to valve metals are those that have metallic conductivity, which can be oxidized and whose oxide layer provides the aforementioned properties. For example, NbO exhibits metallic conductivity but is not generally considered a valve metal. However, the layer of oxidized NbO exhibits the typical properties of valve metal oxide layers, making NbO or alloys or compounds of NbO with other elements typical examples of such compounds having electrical properties equivalent to valve metals. Electrode materials made of tantalum, aluminum, and such electrode materials based on niobium or niobium oxide are preferred. Aluminum is a particularly preferred electrode material.
[0155] To fabricate porous electrode bodies that often have porous regions, valve metal can be sintered in powder form to provide a generally porous electrode body, for example, or alternatively, the porous structure can be imprinted onto a metal body. The latter can be implemented, for example, by etching a film.
[0156] In the following text, for simplicity, a body having porous regions will also be referred to as porous. For example, an electrode body having porous regions will also be referred to as a porous electrode body. On the one hand, a porous body can be permeated by multiple channels and is therefore sponge-like. This is often the case when tantalum is used in the construction of a capacitor. On the other hand, pores can exist only at the surface, and the region disposed below the surface pores can be formed in a solid manner. This is often observed when aluminum is used in the construction of a capacitor.
[0157] The porous electrode body manufactured in this way is then oxidized by applying a voltage, for example, in an aqueous solution of a suitable electrolyte, such as phosphoric acid or ammonium adipate, to form a dielectric. The magnitude of this formation voltage depends on the thickness of the oxide layer to be achieved or, respectively, the subsequent operating voltage of the capacitor. Preferred formation voltages are in the range of 1V to 1000V, particularly preferably in the range of 10V to 200V, more preferably in the range of 15V to 100V, and even more preferably in the range of 20V to 50V.
[0158] The porous electrode body used preferably has a porosity of 10% to 90%, more preferably 30% to 80%, particularly preferably 50% to 80%, and an average pore size of 10 nm to 10000 nm, preferably 50 nm to 5000 nm, particularly preferably 100 nm to 3000 nm.
[0159] According to a specific embodiment of the method of the present invention, the electrolytic capacitor to be manufactured is an aluminum wound capacitor. In this case, in step A), a porous aluminum film as an electrode material is anoly formed, thereby forming an alumina coating as a dielectric. The aluminum film thus obtained (anode film) is then provided with contact lines and wound with another porous aluminum film (cathode film), which is also provided with contact lines, thereby separating the two films from each other by one or more sheets of separating paper, which are based on, for example, cellulose or preferably synthetic paper. After winding, the anode body obtained in this way is fixed, for example, by means of adhesive tape. The one or more sheets of separating paper can be carbonized by heating in an oven. This method of manufacturing the anode body of an aluminum wound capacitor is well known from the prior art and is described, for example, in US 7,497,879B2.
[0160] Method steps B) and C) :
[0161] In method step B) of the method according to the invention, a dispersion according to the invention, preferably a dispersion according to the invention as defined in any one of the first to fourteenth embodiments, or a dispersion obtainable by method 1 according to the invention, preferably by method 1 as defined in any one of the first to ninth embodiments, is introduced into at least a portion of the porous electrode body provided in method step A). Then, in method step C), the dispersant i) is at least partially removed to form a solid electrolyte layer that at least partially covers the surface of the dielectric layer.
[0162] The dispersion is introduced into the porous region using known methods such as immersion, impregnation, pouring, dripping, injection, spraying, spreading, brushing, or printing (e.g., inkjet printing, screen printing, or pad printing). This introduction is preferably carried out by immersing the porous electrode body provided in step A) into the dispersion and thus impregnating it with the dispersion. Immersion in or impregnation with the dispersion is preferably carried out for a duration in the range of 1 second to 120 minutes, particularly preferably in the range of 10 seconds to 60 minutes, and most preferably in the range of 30 seconds to 15 minutes. Introducing the dispersion into the anode body can be facilitated, for example, by increasing or decreasing pressure, vibration, ultrasound, or heat.
[0163] After the porous electrode body has been impregnated with the dispersion as described above, the dispersant i) is at least partially removed in method step C), resulting in the formation of a solid electrolyte layer that partially or completely covers the dielectric. In this context, it is preferred that the solid electrolyte layer covers at least 50% of the dielectric, particularly preferably at least 70%, and most preferably at least 80%, wherein the capacitance of the capacitor under dry and humid conditions at 120°C can be determined as described in DE-A-10 2005 043 828.
[0164] Removal of dispersant i) is preferably carried out by removing the porous electrode body from the dispersion used in step B) and subsequently drying, wherein the drying is preferably carried out at a temperature in the range of 20°C to 200°C, particularly preferably in the range of 50°C to 180°C, and more preferably in the range of 80°C to 150°C. The drying conditions (i.e., drying time, drying pressure, and drying temperature) are preferably adjusted to ensure that at least 50% by weight, more preferably at least 75% by weight, even more preferably at least 90% by weight, even more preferably at least 95% by weight, and most preferably at least 99% by weight of the total amount of dispersant i) is removed when forming the solid electrolyte layer. In a particularly preferred embodiment of the method according to the invention, the drying conditions are adjusted to ensure that the dispersant i) is completely removed when forming the solid electrolyte layer.
[0165] Method step D) :
[0166] In step D), a dispersion containing a conductive polymer, preferably a dispersion containing polythiophene and a dispersant, more preferably a dispersion containing particles of a dispersant and a complex of polythiophene and a polymeric anion, and even more preferably a PEDOT / PSS dispersion, may be applied to at least a portion of the surface of the solid electrolyte layer, followed by at least partial removal of the dispersant to form a polymeric outer layer that at least partially covers the surface of the solid electrolyte layer (as disclosed, for example, in DE10 2004 022 674 A1). As used herein, the term "polymeric outer layer" preferably refers to an outer layer that, although it may contain the exact same conductive polymer as the solid electrolyte layer, differs from the solid electrolyte layer in, for example, chemical composition, conductivity, and / or properties such as hardness, surface roughness, adhesion, etc. Typically, a polymeric outer layer with a thickness ranging from 5 μm to 50 μm serves as a mechanical buffer between the anode and cathode side contacts of the capacitor, thereby preventing the cathode side contacts from contacting the dielectric under mechanical stress that may occur during capacitor manufacturing.
[0167] Before applying the dispersion containing the conductive polymer to at least a portion of the surface of the solid electrolyte layer in step D), a crosslinking agent may advantageously be applied to at least a portion of the surface of the solid electrolyte layer to improve the coverage of the polymer outer layer on the capacitor anode. Suitable crosslinking agents and methods of application thereof are disclosed, for example, in DE 10 2009 007594 A1.
[0168] Method step E) :
[0169] In method step E) of the method according to the invention, at least a portion of the pores of the porous electrode body obtained in method step C) (i.e., the porous electrode body in which the dielectric layer at least partially covers the solid electrolyte layer) may be filled with an impregnation solution containing at least one impregnation solvent.
[0170] Immersion in or separately in the impregnation solution is preferably carried out for a duration ranging from 1 second to 120 minutes, particularly preferably from 10 seconds to 60 minutes, and most preferably from 30 seconds to 15 minutes. Immersion is preferably carried out by at least partially immersing the porous electrode body obtained in step C) in the impregnation solution, or by injecting the impregnation solution into the porous electrode body and impregnating it accordingly. The introduction of the impregnation solution into the porous electrode body can be facilitated, for example, by increasing or decreasing pressure, vibration, ultrasound, or heat.
[0171] In method step E), it is particularly preferred that the impregnation solution be applied immediately before performing method step F) as described below, i.e., before encapsulating the porous electrode body, to prevent the impregnation solvent from evaporating from the pores. Therefore, the impregnation solution applied in method step E) is at least partially, and preferably completely, retained within the pores of the porous electrode body before encapsulating the porous electrode body.
[0172] Examples of impregnation solvents include sulfone compounds, lactone compounds, carbonate compounds, and polyols. Impregnation solvents can be used alone or in combination of two or more of them.
[0173] Examples of sulfone compounds include sulfolane, dimethyl sulfoxide, and diethyl sulfoxide. Examples of lactone compounds include γ-butyrolactone and γ-valerolactone. Examples of carbonate compounds include dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, ethylene carbonate, propylene carbonate, and fluoroethylene carbonate. Examples of polyols include glycerol compounds, sugar alcohol compounds, and diol compounds. Examples of glycerol compounds include glycerol, polyglycerols (diglycerol, triglycerol, etc.), and their derivatives. Examples of diol compounds include alkylene glycols (C2-4 alkylene glycols (ethylene glycol, propylene glycol, etc.) etc.), polyalkylene glycols (polyC2-4 alkylene glycols (diethylene glycol, dipropylene glycol, triethylene glycol, polyethylene glycol, etc.) etc.).
[0174] The impregnation solution may include a solute. Examples of solutes include acidic components such as carboxylic acids, sulfuric acids, boric acids, and phosphoric acids, and basic components such as ammonia, amines, quaternary ammonium compounds, and amidines. Compounds.
[0175] The liquid component may comprise an acid component and a base component, either in a free state or in salt form. The liquid component may include organic salts. Examples of organic salts include those in which at least one of the acid component and the base component is organic.
[0176] The concentration of solute in the liquid component is, for example, in the range of 0.1% by mass to 25% by mass (inclusive), and may be in the range of 0.5% by mass to 15% by mass (inclusive).
[0177] Encapsulation in method step F) :
[0178] After removing at least a portion of the dispersant i) in method step C), or if method steps D) and / or E) are performed, after applying the polymer outer layer in method step D), or after filling at least a portion of the pores of the porous electrode body obtained in method step C) with an impregnation solution in method step E), the electrolytic capacitor can be completed, particularly encapsulated, in a manner known to those skilled in the art. In the case of a tantalum electrolytic capacitor, the capacitor body can be coated, for example, with a graphite layer and a silver layer as known from DE-A-10 2005 043 828, while in the case of an aluminum wound capacitor corresponding to the teachings of US 7,497,879 B2, the capacitor body is built into an aluminum cup provided with sealing rubber and mechanically securely closed by flange processing.
[0179] Encapsulation is preferably achieved by sealing the capacitor body with a resin (such as epoxy resin or thermoplastic resin, as disclosed in EP 0 447 165 A2). In the case of aluminum electrolytic capacitors, encapsulation is preferably achieved by providing an aluminum cup for the porous electrode body obtained in method step e) and closing the aluminum cup with sealing rubber.
[0180] The features disclosed in the claims, specification and drawings may be essential for different embodiments of the claimed invention, whether individually or in any combination of each other. Attached Figure Description
[0181] The following schematic diagrams illustrate aspects of the invention to improve the understanding of the invention in conjunction with some exemplary illustrations.
[0182] Figure 1 The structure of a layered body 100 prepared by the method for preparing a layered structure according to the present invention is shown in a general form, such as an antistatic film. In the case of an antistatic film that is typically a PE, PP, or PET layer, a conductive layer 102 prepared with the composition according to the present invention is placed on the substrate surface of the substrate 101.
[0183] Figure 2 A schematic cross-sectional view is shown through a portion of a capacitor obtained by a specific embodiment of the method for preparing a layered structure according to the invention. The capacitor includes a porous electrode body 101a comprising pores 103, the porous electrode body being primarily made of a porous electrode material 101b, such as aluminum. On the surface of the electrode material 101b, a dielectric layer 101c is formed as a thin layer, thereby forming a still porous anode body comprising the electrode body 101a made of the electrode material 101b and the dielectric layer 101c. On the dielectric layer 101c, optionally following other layers, a solid electrolyte layer 102a (which has been prepared using a dispersion according to the invention) is then formed, thereby forming a capacitor body comprising the electrode body 101a made of the electrode material 101b, the dielectric layer 101c, and the solid electrolyte layer 102a.
[0184] Measurement method :
[0185] Solid content
[0186] Weigh an empty weighing bottle (50 mm in diameter) with a cap using an analytical balance (weight A). Add approximately 5 g of the dispersion to the empty weighing bottle and weigh it with the cap on (weight B). Transfer the opened weighing bottle and cap separately to a drying oven and dry at 100°C for 15 to 16 hours.
[0187] After drying, seal the weighing bottle directly with the cap and cool to room temperature with the cap on. Then weigh the weighing bottle together with the cap on. (Weight C) Repeat the measurement a second time with a new sample.
[0188] The solid content is calculated using the following formula:
[0189] The weight percentage of solids is calculated as follows: (CA) × 100 / (BA).
[0190] Solid content measurements are performed as two separate measurements. The maximum allowable difference between these two solid content measurements is 0.03%. If the difference is large, the measurements must be repeated.
[0191] The final value is the average of two separate measurements.
[0192] Electrical conductivity
[0193] To measure conductivity, 19 g of the dispersion to be analyzed was mixed with 1 g of DMSO in a flask and stirred for 10 minutes. Conductivity is the reciprocal of resistivity. Resistivity is calculated by multiplying the surface resistance of the conductive polymer layer by the layer thickness. The surface resistance of the conductive polymer was determined according to DIN EN ISO 3915. The mixture of polymer dispersion and DMSO was applied as a uniform film onto a thoroughly cleaned glass substrate measuring 50 mm × 50 mm using a spin coater. The coating composition was applied to the substrate using a pipette to completely cover the area and then directly peeled off by spin coating. The spin coating composition was rotated in air at approximately 1,000 rpm for 20 seconds. It was then dried on a hot plate (in air at 130°C for 15 minutes). A 2.0 cm long silver electrode was vapor-deposited onto the polymer layer at a distance of 2.0 cm using a shadow mask. The square area of the layer between the electrodes was then electrically separated from the rest of the layer by drawing two lines with a scalpel. The surface resistance between the Ag electrodes was measured using an ohmmeter (Keithley 614). The thickness of the polymer layer at the crossed-out locations was determined using a stylus profilometer (Dektac 150, Veeco).
[0194] Determination of the power law exponent n
[0195] The power law exponent n was measured using a Haake RV 1 rheometer with a thermostat (as supplied by Haake), a PC with Rheo Win Pro software, a cup and rotor for a dual-gap cylindrical system DG 43 (as supplied by Haake).
[0196] Before the first measurement, set the zero value once a day. Place a dry, clean cup into the rheometer and press it into the unit with your palm. Then secure it using the retaining rod. Secure the rotor to the top using appropriate screws. Turn on the computer and then launch the software "Rheo Win Jobmanager". Open the program, select "Manual Use", and then open "Set Zero Value". Then automatically set the zero value and close the "Manual Use" unit.
[0197] Set the thermostat so that the temperature reading in the rheometer is at 20.0°C. The temperature needs to be within the range of 20.0°C ± 0.2°C. Fill the gap in a dry and clean cup with 12.0 ± 0.3 ml of the dispersion to be analyzed. Secure the cylinder and rotor in the rheometer. The procedure for determining the power exponent n includes the following steps:
[0198] 1) Rotate at 20.0℃, with a deviation of + / -0.2℃, for 120s, at a shear rate of 20 1 / s.
[0199] 2) A rotating ramp at 20.0℃, increasing from 20 1 / s to 1000 1 / s within 100s.
[0200] 3) Rotational ramp regression based on the Ostwald de Waele model selected on Rheo Win Job Manager.
[0201] Record the value of the power exponent n based on the regression measurement using Rheo Win software.
[0202] Determination of particle size (d 50 )
[0203] The particle size was determined as published by HG Müller in Colloid Polym. Sci. 267, 1113-1116 (1989). The diameter distribution d 50 The value indicates that 50% of the total weight of all conductive polymer particles in the dispersion can be attributed to particles with a diameter less than or equal to d. 50 - those particles with value.
[0204] Equivalent series resistance (ESR)
[0205] The equivalent series resistance (in mΩ) was determined at 20°C and 100 kHz using an LCR meter (Agilent 4284A). In each capacitor experiment, three capacitors were fabricated and the average ESR value was determined.
[0206] Examples
[0207] Example 1
[0208] An initial charge of 1,711 g of deionized water and 660 g of polystyrene sulfonic acid aqueous solution (average molecular weight Mw: 70,000 g / mol; solid content: 3.8 wt%; total PSS solids: 25.1 g) was introduced into a 3 L stainless steel reactor equipped with a stirrer, vent, top material inlet, internal thermometer, ultra-turrax, bottom material outlet, and a temperature jacket connected to a thermostat. The reaction temperature was maintained at 18 °C. The mixture was purged with nitrogen for 3 h. The mixture was then evacuated to 33 hPas. 10.2 g of 3,4-ethylenedioxythiophene (71.8 mmol) was added with stirring and turrax. The solution was stirred for 30 min. Subsequently, 0.06 g of ferric sulfate (III) and 19.0 g of sodium persulfate (79.8 mmol) dissolved in 25 g of water were added, and the solution was stirred again under reduced pressure for 23 h.
[0209] This corresponds to an oxidant:monomer ratio of 1.11 and a PEDOT fraction of 28.6% by weight.
[0210] After the reaction was complete, inorganic salts were removed using 200 ml of strongly acidic cation exchanger (Lewatit S108H, Lanxess AG) and 500 ml of weakly basic anion exchanger (Lewatit MP62, Lanxess AG), and the solution was stirred for another 2 hours. The ion exchanger was then filtered out.
[0211] The poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid dispersion was homogenized three times using a high-pressure homogenizer at a pressure of 1000 bar. The resulting "dispersion 1A" exhibited the following properties:
[0212] Solid content: 1.2% by weight
[0213] Dispersion 1A was concentrated, and then 200g of the concentrated dispersion was homogenized 110 times at 1500 bar using a high-pressure homogenizer. Subsequently, 150g of the dispersion was subjected to sonication for 10 min (Hielscher UP 200s, 100%, cycle 1). The resulting dispersion was designated "Dispersion 1B".
[0214] 2 g of ethylene glycol was added to 47.9 g of dispersion 1B. The pH of the mixture was adjusted to 6 using an aqueous solution of ammonium hydroxide. The resulting dispersion 1C (according to the present invention) exhibits the following properties:
[0215] Solid content: 1.8% by weight
[0216] Power exponent n: 0.740
[0217] Electrical conductivity: 336 S / cm
[0218] Example 2
[0219] In the reactor described in Example 1, 2,108 g of water, 153 g of polystyrene sulfonic acid (Mw 70,000 g / mol; 25% solids; 38.3 g total PSS solids), and 6.5 g of 10% ferric sulfate (III) solution were placed. The reaction temperature was maintained at 18 °C. The mixture was purged with nitrogen for 3 h. The mixture was then evacuated to 33 hPas. 6.4 g of 3,4-ethylenedioxythiophene (45 mmol) was added under stirring and turrax. The solution was stirred for 30 min. Subsequently, 12.5 g of sodium persulfate (52.5 mmol) dissolved in 32 g of water was added, and the solution was stirred again under reduced pressure for 23 h. This corresponds to an oxidant:monomer ratio of 1.11 and a PEDOT fraction of 14.3%.
[0220] After the reaction was complete, inorganic salts were removed using 188 g of a strongly acidic cation exchanger (Lewatit S108H, Lanxess AG) and 148 g of a weakly basic anion exchanger (Lewatit MP62, Lanxess AG), and the solution was stirred for another 2 hours. The ion exchangers were then filtered out.
[0221] The poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid dispersion was homogenized three times using a high-pressure homogenizer at a pressure of 1,000 bar. The resulting "dispersion 2A" exhibited the following properties:
[0222] Solid content: 1.6% by weight
[0223] Dispersion 2A was concentrated, and then 200g of the concentrated dispersion was homogenized 60 times at 1,500 bar using a high-pressure homogenizer. The resulting dispersion was designated "Dispersion 2B".
[0224] 2 g of ethylene glycol was added to 47.9 g of dispersion 2B. The pH of the mixture was adjusted to 6 using an aqueous solution of ammonium hydroxide. The resulting dispersion 2C (according to the present invention) exhibited the following properties.
[0225] Solid content: 1.8% by weight
[0226] Power exponent n: 0.802
[0227] Electrical conductivity: 148 S / cm
[0228] Example 3
[0229] 1,686 g of deionized water and 660 g of polystyrene sulfonic acid aqueous solution (Mw 70,000 g / mol; solids content 3.8 wt%; total PSS solids 25.1 g) were charged into the reactor described in Example 1. The reaction temperature was maintained at 18 °C. The mixture was purged with nitrogen for 3 h. The mixture was then evacuated to 33 hPas. 10.2 g of 3,4-ethylenedioxythiophene (71.8 mmol) was added under stirring and turrax. The solution was stirred for 30 min. Subsequently, 0.06 g of ferric sulfate (III) and 20.9 g of sodium persulfate (87.8 mmol) dissolved in 50 g of water were added, and the solution was stirred and dispersed again under reduced pressure for 23 h. This corresponds to an oxidant:monomer ratio of 1.22 and a PEDOT fraction of 28.6%.
[0230] After the reaction was complete, inorganic salts were removed using 200 ml of strongly acidic cation exchanger (Lewatit S108H, Lanxess AG) and 500 ml of weakly basic anion exchanger (Lewatit MP 62, Lanxess AG), and the solution was stirred for another 2 hours. The ion exchanger was then filtered out.
[0231] The poly(3,4-ethylenedioxythiophene) / polystyrene sulfonic acid dispersion was homogenized three times using a high-pressure homogenizer at a pressure of 1000 bar. The resulting "dispersion 3A" exhibited the following properties:
[0232] Solid content: 1.2% by weight
[0233] Dispersion 3A was concentrated, and then 200g of the concentrated dispersion was homogenized 100 times at 1,500 bar using a high-pressure homogenizer. The resulting dispersion was designated "Dispersion 3B".
[0234] 2 g of ethylene glycol was added to 47.9 g of dispersion 3B. The pH of the mixture was adjusted to 6 using an aqueous solution of ammonium hydroxide. The resulting dispersion 3C (according to the present invention) exhibits the following properties:
[0235] Solid content: 1.8% by weight
[0236] Power exponent n: 0.776
[0237] Electrical conductivity: 186 S / cm
[0238] Example 4
[0239] 100 g of dispersion 1A was placed in a glass bottle and sonicated for 30 min (Hielscher UP 200S, 100%, cycle 1). The dispersion was then concentrated to 1.8% by weight. Subsequently, 30 g of the dispersion was sonicated again for 45 min (Hielscher UP 200S, 100%, cycle 1). During sonication, the glass bottle containing the dispersion was placed in a water bath, and the temperature was maintained between 15°C and 45°C. The mixture was then cooled to room temperature. 1 g of ethylene glycol was added to 23.95 g of the sonicated dispersion. The pH of the mixture was adjusted to 6 using an aqueous solution of ammonium hydroxide. The resulting "dispersion 4C" (not according to the invention) exhibited the following properties:
[0240] Solid content: 1.8% by weight
[0241] Power exponent n: 0.941
[0242] Electrical conductivity: 154 S / cm
[0243] Example 5
[0244] 400g of the same dispersion as dispersion 1A was concentrated, and then 200g of the concentrated dispersion was homogenized 10 times at 1,500 bar using a high-pressure homogenizer. The resulting dispersion is "dispersion 5B".
[0245] 2 g of ethylene glycol was added to 47.9 g of dispersion 5B. The pH of the mixture was adjusted to 6 using an aqueous ammonium hydroxide solution. The resulting dispersion 5C (not according to the invention) exhibited the following properties:
[0246] Solid content: 1.8% by weight
[0247] Power exponent n: 0.610
[0248] Electrical conductivity: 362 S / cm
[0249] Example 6 (not according to the invention)
[0250] 100 g of the same dispersion as dispersion 1A was placed in a glass bottle and subjected to sonication for 30 min (Hielscher UP 200S, 100%, cycle 1). The dispersion was then concentrated to 1.5% by weight. Subsequently, 30 g of the dispersion was sonicated for 30 min (Hielscher UP 200S, 100%, cycle 1). During sonication, the glass bottle containing the dispersion was cooled in a water bath, and the temperature in the container was maintained between 15°C and 40°C. 1 g of ethylene glycol was added to 23.95 g of the sonicated dispersion. The pH of the mixture was adjusted to 6 using an aqueous solution of ammonium hydroxide. The resulting "dispersion 6C" (not according to the invention) exhibits the following properties:
[0251] Solid content: 1.5% by weight
[0252] Power exponent n: 0.964
[0253] Electrical conductivity: 175 S / cm
[0254] Example 7
[0255] 400g of the same dispersion as dispersion 1A was concentrated, and then 200g of the concentrated dispersion was homogenized 65 times at 1,500 bar using a high-pressure homogenizer. Then, 150g of the dispersion was subjected to sonication for 10 min (Hielscher UP 200s, 100%, cycle 1). The resulting dispersion was designated "Dispersion 7B".
[0256] 2 g of ethylene glycol was added to 47.9 g of dispersion 7B. The pH of the mixture was adjusted to 6 using an aqueous solution of ammonium hydroxide. The resulting dispersion 7C (according to the present invention) exhibits the following properties:
[0257] Solid content: 1.5% by weight
[0258] Power exponent n: 0.751
[0259] Electrical conductivity: 214 S / cm
[0260] Example 8
[0261] 400g of the same dispersion as dispersion 1A was concentrated, and then 200g of the concentrated dispersion was homogenized 35 times at 1,500 bar using a high-pressure homogenizer. The resulting dispersion was designated "dispersion 8B".
[0262] 2 g of ethylene glycol was added to 47.9 g of dispersion 8B. The pH of the mixture was adjusted to 6 using an aqueous ammonium hydroxide solution. The resulting dispersion 8C (not according to the invention) exhibited the following properties:
[0263] Solid content: 1.5% by weight
[0264] Power exponent n: 0.613
[0265] Electrical conductivity: 305 S / cm
[0266] Example 9
[0267] 400g of dispersion 1A was homogenized 10 times at 1,500 bar using a high-pressure homogenizer. The resulting dispersion was designated "Dispersion 9B".
[0268] 2 g of ethylene glycol was added to 47.9 g of dispersion 9B. The pH of the mixture was adjusted to 6 using an aqueous solution of ammonium hydroxide. The resulting dispersion 9C (not according to the invention) exhibited the following properties:
[0269] Solid content: 1.2% by weight
[0270] Power exponent n: 0.610
[0271] Electrical conductivity: 364 S / cm
[0272] Example 10
[0273] 400g of dispersion 1A was homogenized 45 times at 1,500 bar using a high-pressure homogenizer. The resulting dispersion was designated "Dispersion 10B".
[0274] 2 g of ethylene glycol was added to 47.9 g of dispersion 10B. The pH of the mixture was adjusted to 6 using an aqueous solution of ammonium hydroxide. The resulting dispersion 10C (not according to the invention) exhibited the following properties:
[0275] Solid content: 1.2% by weight
[0276] Power exponent n: 0.781
[0277] Electrical conductivity: 378 S / cm
[0278] Example 11
[0279] 400g of dispersion 1A was homogenized 125 times at 1,500 bar using a high-pressure homogenizer. The resulting dispersion is called "Dispersion 11B".
[0280] 2 g of ethylene glycol was added to 47.9 g of dispersion 11B. The pH of the mixture was adjusted to 6 using an aqueous solution of ammonium hydroxide. The resulting dispersion 11C (not according to the invention) exhibited the following properties:
[0281] Solid content: 1.2% by weight
[0282] Power exponent n: 0.950
[0283] Electrical conductivity: 356 S / cm
[0284] Example 12
[0285] 200g of dispersion 2B was homogenized 20 times. The resulting dispersion was designated "dispersion 12B". 2g of ethylene glycol was added to 47.9g of dispersion 12B. The pH of the mixture was adjusted to 6 using an aqueous solution of ammonium hydroxide. The resulting "dispersion 12C" (according to the present invention) exhibited the following properties.
[0286] Solid content: 1.8% by weight
[0287] Power exponent n: 0.891
[0288] Electrical conductivity: 146 S / cm
[0289] Example 13
[0290] 400 g of the same dispersion as dispersion 1A was concentrated, and then 200 g of the concentrated dispersion was homogenized 65 times at 1500 bar using a high-pressure homogenizer. Then, 150 g of the dispersion was subjected to sonication for 3 min (Hielscher UP 200S, 100%, cycle 1). The resulting dispersion was designated "Dispersion 13B". 2 g of ethylene glycol was added to 47.9 g of dispersion 13B. The pH of the mixture was adjusted to 6 using an aqueous solution of ammonium hydroxide. The resulting "Dispersion 13C" (according to the invention) exhibited the following properties.
[0291] Solid content: 1.5% by weight
[0292] Power exponent n: 0.652
[0293] Electrical conductivity: 220 S / cm
[0294] Table 1 summarizes the results of examples 1 to 13 :
[0295]
[0296] i = according to the present invention; ni = not according to the present invention
[0297] Process for producing a capacitor
[0298] Method step A) :
[0299] Cylindrical aluminum capacitors with a rated voltage of 25V are manufactured in the following manner (e.g.) Figure 2A porous electrode body (as described in the text) is formed. An aluminum foil is etched to roughen its surface. The aluminum foil is then anodized using an aqueous solution of ammonium adipate to form a dielectric layer on its surface. Thus, an anode foil is produced.
[0300] The second aluminum foil is etched to roughen its surface. Thus, the cathode foil is prepared.
[0301] Anode and cathode leads are connected to the anode and cathode foils, respectively. The anode and cathode foils are wound together, with two sheets of release paper between them. Adhesive tape is placed on the outside of the wound element to prevent the foils from unwinding. The wound element is then subjected to another anodizing process to form a dielectric layer on the cut edge of the anode foil.
[0302] Therefore, an anode body comprising an electrode body having a dielectric layer was prepared.
[0303] Method step B) :
[0304] The porous electrode body from step A) is placed in a chamber containing a liquid composition comprising a conductive polymer. The air pressure in the chamber is reduced to 100 hPa. The anode body is immersed in the liquid composition for 300 s. Then, the anode body is removed from the liquid composition and the chamber is evacuated to atmospheric pressure.
[0305] Method step C)
[0306] Dry the anode body at 120°C for 30 minutes.
[0307] Steps B) and C) are performed again. Thus, a capacitor body containing a PEDOT / PSS-based solid electrolyte layer is obtained.
[0308] Method step F)
[0309] The capacitor body of step C) is placed in a cylindrical aluminum casing and sealed with a rubber seal.
[0310] Example 14
[0311] First, a first anode body is prepared according to method step A). Then, the anode body is treated with dispersion 1C of Example 1 according to method steps B) and C) to form a solid electrolyte layer. Method steps B) and C) are repeated once more. Thus, a capacitor body is obtained. The capacitor body is packaged according to method step F) to obtain a finished capacitor. The average ESR of the capacitor (according to the present invention) is given in Table 2.
[0312] Example 15
[0313] The capacitors were produced and evaluated in the same manner as in Example 14; however, the solid electrolyte layer was formed using dispersion 2C from Example 2. The average ESR of the capacitors (according to the present invention) is given in Table 2.
[0314] Example 16
[0315] The capacitors were produced and evaluated in the same manner as in Example 14; however, the solid electrolyte layer was formed using the dispersion 3C of Example 3. The average ESR of the capacitors (according to the present invention) is given in Table 2.
[0316] Example 17
[0317] The capacitors were produced and evaluated in the same manner as in Example 14; however, the solid electrolyte layer was formed using dispersion 4C from Example 4. The average ESR of the capacitors (not according to the invention) is given in Table 2.
[0318] Example 18
[0319] The capacitors were produced and evaluated in the same manner as in Example 14; however, the solid electrolyte layer was formed using dispersion 5C from Example 5. The average ESR of the capacitors (not according to the present invention) is given in Table 2.
[0320] Example 19
[0321] The capacitors were produced and evaluated in the same manner as in Example 14; however, the solid electrolyte layer was formed using the dispersion 6C of Example 6. The average ESR of the capacitors (not according to the present invention) is given in Table 2.
[0322] Example 20
[0323] The capacitors were produced and evaluated in the same manner as in Example 14; however, the solid electrolyte layer was formed using the dispersion 7C of Example 7. The average ESR of the capacitors (according to the present invention) is given in Table 2.
[0324] Example 21
[0325] The capacitors were produced and evaluated in the same manner as in Example 14; however, the solid electrolyte layer was formed using dispersion 8C from Example 8. The average ESR of the capacitors (not according to the invention) is given in Table 2.
[0326] Example 22
[0327] The capacitors were produced and evaluated in the same manner as in Example 14; however, the solid electrolyte layer was formed using the dispersion 9C of Example 9. The average ESR of the capacitors (not according to the present invention) is given in Table 2.
[0328] Example 23
[0329] The capacitors were produced and evaluated in the same manner as in Example 14; however, the solid electrolyte layer was formed using the dispersion 10C of Example 10. The average ESR of the capacitors (not according to the invention) is given in Table 2.
[0330] Example 24
[0331] The capacitors were produced and evaluated in the same manner as in Example 14; however, the solid electrolyte layer was formed using the dispersion 11C of Example 11. The average ESR of the capacitors (not according to the present invention) is given in Table 2.
[0332] Example 25
[0333] The capacitors were produced and evaluated in the same manner as in Example 14; however, the solid electrolyte layer was formed using the dispersion 12C of Example 12. The average ESR of the capacitors (according to the present invention) is given in Table 2.
[0334] Example 26
[0335] The capacitors were produced and evaluated in the same manner as in Example 14; however, the solid electrolyte layer was formed using dispersion 13C from Example 13. The average ESR of the capacitors (according to the present invention) is given in Table 2.
[0336] Table 2 summarizes the results of examples 14 to 26 :
[0337]
[0338] i = according to the present invention; ni = not according to the present invention
[0339] Reference number index
[0340]
Claims
1. A dispersion comprising: i) Dispersant; ii) At least one polythiophene dispersed in the dispersant i); For a dispersion, the power-law exponent n in the Ostwald de Waele relation is... In the range of 0.62 to 0.92, among which It is shear stress, K is the flow consistency index, and It is the shear rate dγ / dt; and The dispersion has a solid content of at least 1.5% by weight based on the total weight of the dispersion.
2. The dispersion according to claim 1, wherein the power law exponent n is in the range of 0.66 to 0.
88.
3. The dispersion according to claim 2, wherein the power law exponent n is in the range of 0.70 to 0.
84.
4. The dispersion according to any one of claims 1 to 3, wherein the dispersion has a solid content of at least 1.7% by weight based on the total weight of the dispersion.
5. The dispersion according to any one of claims 1 to 4, wherein the dispersant i) comprises water.
6. The dispersion according to any one of claims 1 to 5, wherein the polythiophene exists in the form of particles comprising a complex of the polythiophene and a polyanion.
7. The dispersion according to claim 6, wherein the polythiophene is poly(3,4-ethylenedioxythiophene), and wherein the polyanion is the anion of polystyrene sulfonic acid.
8. The dispersion according to any one of claims 1 to 7, wherein the polythiophene exists in the form of particles comprising a complex of the polythiophene and the polyanion, and wherein the solid content as defined in claims 1 and 4 refers to the total amount of the polythiophene and the polyanion in the dispersion.
9. The dispersion according to any one of claims 1 to 8, wherein the conductivity of the conductive layer prepared from said dispersion is at least 100 S / cm, as determined by the test methods disclosed herein.
10. The dispersion according to any one of claims 1 to 9, wherein the dispersion further comprises iii) Conductivity improvers.
11. A method for preparing a layered body (100), the method comprising the following steps: A) Provide a substrate (101); B) Applying the dispersion according to any one of claims 1 to 10 to at least a portion of the surface of the substrate (101); C) At least partially remove the dispersant i) to obtain a layer (100) comprising a conductive layer (102) coated on at least a portion of the surface of the substrate (101).
12. The method of claim 11, wherein the layer (100) is part of an electrolyte capacitor, wherein the substrate (101) is a porous electrode body (101a) made of electrode material (101b), wherein a dielectric layer (101c) at least partially covers the surface of the electrode material (101b), and wherein the conductive layer (102) is a solid electrolyte layer (101d) at least partially covering the surface of the dielectric layer (101d).
13. The method of claim 12, wherein the method comprises the following steps: A) Provides a porous electrode body (101a) made of electrode material (101b), wherein a dielectric layer (101c) at least partially covers the surface of the electrode material (101b); B) Introducing the dispersion according to any one of claims 1 to 10 into at least a portion of the porous electrode body (101a) provided in step A) of the method in order to apply the dispersion to at least a portion of the surface of the dielectric layer (101c); C) At least partially remove the dispersant i) to form a solid electrolyte layer (101d) that at least partially covers the surface of the dielectric layer (101c).
14. A layered body that can be obtained by the method according to any one of claims 11 to 13.
15. Use of the dispersion according to any one of claims 1 to 10 for forming a solid electrolyte layer in a capacitor.
Citation Information
Patent Citations
Electrolytic condenser for use in electronic circuits, e.g. for computers, comprises porous electrode, dielectric, solid electrolyte and a layer containing a polymeric anion, a polyaniline or polythiophene and a binder
DE102004022674A1
method of manufacturing electrolytic capacitors
DE102005043828A1
Method for manufacturing electrolytic capacitors with a polymer outer layer.
DE102009007594A1
Solid electrolytic capacitors and method for manufacturing the same
EP0447165A2
Heat mode recording element based on a thin metal layer
EP1043720A1
